The Diagnostic Role of Lung Ultrasound and Contrast-Enhanced Ultrasound in Pulmonary Embolism - Boccatonda, Andrea; Andreetto, Lorenzo; Vicari, Susanna; Campello, Elena; Simioni, Paolo; Ageno, Walter (Seminars in Thrombosis and Hemostasis, 2023)
The diagnosis of pulmonary embolism (PE) relies essentially on a probabilistic approach that requires careful clinical assessments, targeted laboratory tests, and the use of appropriate imaging tools. Nowadays, the diagnostic gold standard is computed tomographic pulmonary angiography. Lung ultrasound (LUS) can play a role in the diagnosis of PE mainly by allowing the visualization of peripheral lung infarctions. Hypoechoic, pleural-based parenchymal consolidation is the most typical and common finding of pulmonary infarction. More than 85% of infarct lesions are wedge-shaped, extending to the pleural surface and are localized to where the patient complains of pleuritic chest pain. Contrast-enhanced ultrasound can be performed in addition to basic ultrasound examination to ascertain nonvascularization of the consolidation, thus confirming that the lesion is an infarct. The aim of this narrative review is to summarize the latest evidence on the application of LUS to the diagnosis of PE, focusing purely on thoracic/lung signs.
Keywords: computed tomographic pulmonary angiography; diagnosis; imaging; pulmonary infarction; venous thromboembolism